ANALISIS FILM KWARTET: GUPALA SANG JAGAWANA - I Kadek Bayu Pramuditya; I Made Krishna Surya Pradnyana; I Gede Agus Indram bayu Artha (Pusat Penerbitan LPPM ISI Bali, 2026)
Kwartet: Gupala Sang Jagawana is an animated film by a local studio called Dipadira in collaboration with Indonesiana tv which was released in 2024. Tells the story of a group of adventurous teenagers named Bagas, Nalin, Juna, Dan, Kara. When Bagas and Juna were playing boy boyan, a tragedy occurred, the ball they used to play hit Nalin who was on the outside of the field, Nalin immediately returned Juna & Bagas' throw but Nalin accidentally dropped the offerings while in an old hermitage in Kalasenja village, making Mbah Arang appear, from behind a tree, suddenly making the children scared and running away, which made them kidnapped into the supernatural world, what is their fate. Some of the main characters are Bagas, Nalin, Juna, Dan, Kara. In order to understand this animated film further, further observation was carried out on the animated film Kwartet: Gupala sang jagawana